Ludwig M. Lachmann Against the Cambridge School - Ferlito, Carmelo (Journal of Reviews on Global Economics, 2015)
While in the early 1930s Keynes and Hayek were the major figures in a heated academic debate about money and capital, in which Keynes also and especially involved the Italian Piero Sraffa, it might seem at first sight that the Austrian economist set aside an organic demolition of the ideas expressed in 1936 by his rival in the General Theory. Hayek himself, in the future, would regret not having devoted an organic work to criticising the new Keynesian theories. However, as demonstrated in Sanz Bas (2011), although it is not possible to find a debate such as the one on the Treatise on Money, Hayek’s subsequent works do include timely and reasoned criticisms as regards the main conclusions of the new Cambridge macroeconomics. But the ’Austrian knight’ of a new Vienna-Cambridge debate, in the subsequent decades, was the German economist Ludwig M. Lachmann (1906-1990), a student of Hayek at LSE during the 1930s and later a professor in Johannesburg and New York. Lachmann was one of the protagonists of the Austrian revival after 1974 and the founding leader of the ’nermeneutic stream’, opposed by the Rothbardian stream. Lachmann, defending Keynes’s subjectivism and expectation theory, revived the Vienna-Cambridge controversy, criticising not Keynes but his followers, in particular the ’new’ Cambridge School, developed by Joan Robinson and Piero Sraffa. Lachmann’s life sight was to build a new economics paradigm, centred on the idea of market process, expectations and kaleidic society (Shackle); in order to do so he developed a deep attack toward the new Cambridge macroeconomics mainstream, arising from World War II ashes during the 1950s and 1960s. His polemic toward the ’modern’ macroeconomics can be read in all his books and papers, but it is particularly evident in Lachmann (1973, [1986a] 1994). His preferred targets were Sraffa and Joan Robinson, ’guilty’, according to Lachmann, to overcome Keynes’s subjectivism and to develop a new Neo-Ricardian approach. The resulting macroeconomics is accused to be excessively formalist, ignoring the microfoundations that are at the very root of human action and choice. But Lachmann’s attack was not only an epistemological one. He intensively tried to demolish all the pillars of the Cambridge macroeconomics: capital as aggregate, long run equilibrium, the absence of innovation and technological change and the conception of rate of profit. His starting point was an economics based on human expectations as the only possible source of human actions. A source, however, never at rest, and continuously influenced by technological change and changing information.